2015
DOI: 10.1186/s12985-015-0242-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of human papillomavirus 16 E6 variants with cervical carcinoma and precursor lesions in women from Southern Mexico

Abstract: BackgroundHPV 16 is the cause of cervical carcinoma, but only a small fraction of women with HPV infection progress to this pathology. Besides persistent infection and HPV integration, several studies have suggested that HPV intratype variants may contribute to the development of cancer. The purpose of this study was to investigate the nucleotide variability and phylogenetically classify HPV 16 E6 variants circulating over a period of 16 years in women from Southern Mexico, and to analyze its association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 44 publications
4
25
0
Order By: Relevance
“…The EUR-350G isolate was 1.5 times more represented than the EUR-350T isolate in this cohort of women, with stability of this ratio (EUR-350T/EUR-350G) existing for the 2012-2015 period, like in other French studies [48]. A small fraction of these lineages contained co-mutations that were previously described [49,50].…”
Section: Discussionsupporting
confidence: 74%
“…The EUR-350G isolate was 1.5 times more represented than the EUR-350T isolate in this cohort of women, with stability of this ratio (EUR-350T/EUR-350G) existing for the 2012-2015 period, like in other French studies [48]. A small fraction of these lineages contained co-mutations that were previously described [49,50].…”
Section: Discussionsupporting
confidence: 74%
“…Similar results were obtained in Slovenian patients with cervical cancer, where mainly European genomic variations of HPV16 were found and only 2/40 (5%) of the cases were associated with non-European HPV16 genomic variants -the Asian-American and African 2 branches (Vrtačnik Bokal et al, 2010). Several studies showed that non-European HPV16 genomic variants (lineage B, C, D) are associated with stronger oncogenic potential than the European line- Xi et al, 2007;Sichero et al, 2007;Schiffman et al, 2010;Freitas et al, 2014;Ortiz-Ortiz et al, 2015). Moreover, the Asian American// North American (AA/NA ) variants were linked to higher capacity of in vitro transformation of human keratinocytes (Sichero et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The European variant lineage is further arranged into several variant sublineages [ 10 , 11 ]. Diverse HPV16 variants have in studies shown to contribute to the development of cervical cancer and precancerous lesions to different degrees [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%